Driving the State : Families and Public Policy in Central Mexico - Byrnes, Dolores M., 1958- (Book collections on Project MUSE., 2003)
In her absorbing ethnography of the everyday practice of public policy, Dolores M. Byrnes focuses on Mi Comunidad, a job-creation program founded in 1996 by Vicente Fox when he was governor of Guanajuato. This program was intended to reduce migration and became an important source of empowerment for small businesses in rural Mexico. A significant aspect of the program is the way it encourages former residents who have successfully migrated to the United States to invest in the maquilas back home. Byrnes's close look at policy implementation reveals changing relationships between families and the state. Working as a volunteer in Mi Comunidad, Byrnes attempted to understand how the program worked. As she traveled from site to site with the two female state employees who implemented the program's policies, she saw that program practices reproduced middle-class values rather than female solidarity. In spite of this, she argues for the potential of female professional power, with implications for democracy and social justice. Perhaps most interesting of all, Byrnes portrays the formation of nonborder maquilas in rich detail and shows how government employees at the local level personally engage in "driving the state."